2019
DOI: 10.3390/rs11091052
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Detection with Historical Geostationary Satellite Sensors for Climate Applications

Abstract: Can we build stable Climate Data Records (CDRs) spanning several satellite generations? This study outlines how the ClOud Fractional Cover dataset from METeosat First and Second Generation (COMET) of the EUMETSAT Satellite Application Facility on Climate Monitoring (CM SAF) was created for the 25-year period 1991-2015. Modern multi-spectral cloud detection algorithms cannot be used for historical Geostationary (GEO) sensors due to their limited spectral resolution. We document the innovation needed to create a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…First, Govaerts et al, (2018) [22] demonstrated the improved identification of deep convective clouds by using the recalibrated IR radiances. Second, Bojanowski et al, (2018) [23] and Stockli et al, (2019) [24] used the recalibrated radiances for deriving cloud fractional cover climatology. Finally, Duguay-Tetzlaf et al, (2017) [25] demonstrated the impact of reduced bias and better temporal stability of the recalibrated radiances on their land surface temperature data record.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Govaerts et al, (2018) [22] demonstrated the improved identification of deep convective clouds by using the recalibrated IR radiances. Second, Bojanowski et al, (2018) [23] and Stockli et al, (2019) [24] used the recalibrated radiances for deriving cloud fractional cover climatology. Finally, Duguay-Tetzlaf et al, (2017) [25] demonstrated the impact of reduced bias and better temporal stability of the recalibrated radiances on their land surface temperature data record.…”
Section: Validationmentioning
confidence: 99%
“…Further, radiances recalibrated with the methods presented in this paper were used in several studies [22][23][24][25] that showed their superiority to operational calibrated radiances. Finally, Tabata et al, (2019) [8] presented a comprehensive validation a full time-series, covering the years 1978-2016, of recalibrated IR and WV radiances from the VISSR, JAMI, IMAGER and Imager instruments onboard JMA's geostationary satellites (paper has been submitted to the same special issue as this paper).…”
mentioning
confidence: 99%
“…For those targets the spectral band adjustment functions can be derived using SCIAMACHY measurements. In order to control the cloudiness of the considered SCIAMACHY spectra, the SEVIRI cloud product is used [2] that also provides an estimate of the cloud-top pressure. To be accepted for the analysis, the footprint of a SCIAMACHY measurement has to be entirely cloud-free (Algeria-3 and Atlantic-1) or homogeneously covered by a cloud with the defined cloud-top-pressure (High-, Mid-and Low-cloud).…”
Section: Comparisons With Sevirimentioning
confidence: 99%
“…The lower and upper hinges correspond to the 25th and 75th percentiles, while whiskers extend from the hinge to the largest and lowest values within 1.5 times the interquartile range. derived using the Theil-Sen estimates (Theil, 1950), and their significance was estimated with the Mann-Kendall test (Kendall, 1938;Mann, 1945). For multiple comparisons of the statistical significance of each grid, we applied the adjustment of the p value using the method of Benjamini and Hochberg (1995).…”
Section: Assessing Errors and Spurious Trends Of The Artificial Avhrrmentioning
confidence: 99%